Analyzing the Reading Literacy Competence of Primary School Teacher Education Students at Universitas Cenderawasih - Mamberuman Marthen Inggamer; Dian Septikasari; Amelia Warikar (SAINTIS Publishing, 2025)
This study aims to analyze the reading literacy skills of second-semester students based on the results of the Even Semester Midterm Assessment in the Indonesian Language and Literature course within the Primary School Teacher Education (PGSD) Program at Universitas Cenderawasih for the 2023/2024 academic year. A qualitative descriptive method was employed, with data collected through tests, interviews, and questionnaires. A total of 200 students from eight different classes participated in the study and were categorized into four literacy proficiency levels: in need of special intervention, basic, proficient, and advanced. The findings reveal variations in students’ reading literacy levels, with 4% categorized as needing special intervention, 30% at the basic level, 44% at the proficient level, and 22% at the advanced level. These literacy levels were measured using midterm test items that assessed three cognitive domains: retrieving information, interpreting and integrating, and evaluating and reflecting. The results indicate that students struggled particularly with cognitive tasks related to evaluation and reflection.These findings offer valuable insights for lecturers, providing a clearer understanding of students’ reading literacy capabilities. This information can serve as a foundation for reflective teaching practices and the formulation of more effective strategies aimed at improving students’ reading literacy—especially their critical and reflective thinking skills.